Family communication and the choice of a life partner among youths in Malaysia - Normah Mustaffa,; Shahrul Nazmi Sannusi,; Ruzian Markom, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Family communication often becomes an important discourse in the discussion on family function as one of an entity in our society. Parents are the pillars in providing a good environment in the family. Communication among family members and siblings is also found affecting the decision-making process and clear communication between parents and child can bring them to a very positive and effective interaction. McLeod and Chaffee (1972) formulated the quadrant family communication pattern framework namely, permissive, pluralistic, prohibitive and protective. Applying this framework, this study aimed to identify patterns of family communication between parents and their children in the choice of a life partner. Using a survey method, questionnaires were distributed to 400 respondents throughout Peninsular Malaysia and analyzed using Statistical Packages for Social Science (SPSS) version 23. The mean analysis was performed to identify the most dominant family communication patterns when discussing marriage matters. The study found that protective family communication pattern showed the highest level of practice among all communication patterns and have proven to be a significant contributor for Malaysian youth on their decisions towards marriage and life partner choices. The results from this study contribute to the understanding of the importance of communication among family in the decision making with regards to marriage. The present study adds to the existing knowledge on the importance of communication among family members and provides direction for future research work in this area.